Sea cucumber species found in Soft-bottom of Wulan Estuary-Demak, Central Java. Issue 1 (December 2021) - Hartati, R; Redjeki, S; Riniatsih, I; Widianingsih, W; Nuraini, R A T; Endrawati, H; Mahendrajaya, RT
Abstract: Indonesia has been known to have a high diversity of sea cucumber, but data and information are mostly on high-economic-value species. Sea cucumber living in soft-bottom substrates is less studied and unexploited. Wulan estuary located in the Demak Regency of Central Java was experiencing high sedimentation, which was consisted of fine material, and acted as a habitat for many macrozoobenthos, amongst others sea cucumbers. The objective of the present research was to identify the species of sea cucumber in the soft bottom of the Wulan estuary. The collection of sea cucumber specimens was done using a dredge. A total of 132 specimens were collected, examined, and identified through their morphological characters. The holothuroids found in the soft-bottom of the Wulan estuary represent five genera (Acaudina, Colochirus, Holothuria, Paracaudina, Phyllophorus, ) in four families (Caudinidae, Cucumariidae, Holothuriidae, and Phyllophoridae) belonging to three orders (Molpadida, Dendrochirotida, and Aspidochirotida). The species were Acaudina sp., A. molpadioides, Colochirus quadrangularis, Holothuria cf. impatiens, Paracaudina sp., Paracaudina chilensis, P. australis, and Phyllophorus spiculata . A. molpadioides is presented as the most frequently found species. Although sea cucumber found in the Wulan estuary has not been exploited, it still needs to be managed to sustain its population.